Beneficial insects move from flowering plants to nearby crops - R Long; A Corbett; C Lamb; C Reberg-Horton; J Chandler; M Stimmann (California Agriculture, 1998)
Marking studies demonstrated that lady beetles, lacewings, syrphid flies and parasitic wasps fed on nectar or pollen provided by borders of flowering plants around farms; many insects moved 250 feet into adjacent field crops. Studies using the elemental marker rubidium also showed that syrphid flies, parasitic wasps and lacewings fed on flowering cover crops in orchards and that some moved 6 feet high in the tree canopy and 100 feet away from the treated area. The use of nectar or pollen by beneficial insects helps them survive and reproduce. Therefore, planting flowering plants and perennial grasses around farms may lead to better biological control of pests in nearby crops.